TEST OF EFFECT KEDONDONG LEAF ETHANOL EXTRACT (SPONDIAS DULCIS) ON STAPHYLOCOCCUS AUREUS BACTERIA - Situmorang, Novidawati Boru; Fatima, Nurdilla; Teresia Marbun, Romauli Anna; Sihombing, Yanna Rotua (Jurnal FARMASIMED (JFM), 2023)
Bacteria that cause infection and disease are commonly found in our environment, one of which is Staphylococcus aureus bacteria. Several infectious diseases are also caused by Staphylococcus aureus, including cellulitis, acne (acne), and infection with Staphylococcal Scalded Skin Syndrome (SSSS). To determine whether the ethanol extract of kedondong leaves (EEDK) has antibacterial activity against Staphylococcus aureus bacteria. This study used a laboratory experimental method with several stages such as sample collection, identification of plants for making simplicia, phytochemical screening, extract preparation and preparation of kedondong leaf extract test solutions with various concentrations of 15%, 25%, 35% and positive control (Chloramphenicol), negative control (DMSO), and antibacterial activity testing using the paper disc method. The results of phytochemical screening of kedondong leaf simplicia (Spondias dulcis) found that kedondong leaves contain secondary metabolites such as alkaloids, flavonoids, tannins and saponins that have the potential to inhibit bacterial growth. % of 9.4 mm, 25% concentration of 13.5 mm and the greatest inhibition was at a concentration of 35% of 19.5 mm. Kedondong leaf extract has antibacterial activity against the growth of Staphylococcus aureus bacteria, with moderate to strong categories. inhibit the activity of Staphylococcus aureus bacteria is a concentration of 35%. Based on the description above, it was found that the EED with a concentration of 35% had the greatest antibacterial effect compared to the concentration of 15% and 25%. and it can be concluded that the higher the concentration of the extract used, the higher the antibacterial effect.